Critical role of the D21S55 region on chromosome 21 in the pathogenesis of Down syndrome. - Rahmani, Z (1989)
The duplication of a specific region of chromosome 21 could be responsible for the main features of Down syndrome. To define and localize this region, we analyzed at the molecular level the DNA of two patients with partial duplication of chromosome 21. These patients belong to two groups of Down syndrome patients characterized by different partial trisomies 21: (i) duplication of the long arm, proximal to 21q22.2, and (ii) duplication of the end of the chromosome, distal to 21q22.2 We assessed the copy number of five chromosome 21 sequences (SOD1, D21S17, D21S55, ETS2, and D21S15) and found that D21S55 was duplicated in both cases. By means of pulsed-field gel analysis and with the knowledge of regional mapping of the probes D21S17, D21S55 and ETS2, we estimated the size of the common duplicated region to be between 400 and 3000 kilobases. This region, localized on the proximal part of 21q22.3, is suspected to contain genes the overexpression of which is crucial in the pathogenesis of Down syndrome.